Blast cell vacuoles in childhood lymphoblastic leukaemia. - Lilleyman, J; Hann, I; Stevens, R; Richards, S; Eden, O (1988)
As part of a central review of cell morphology in childhood lymphoblastic leukaemia (ALL), marrow smears from entrants to the Medical Research Council trial UKALL VIII, other than those from children with B-ALL, were studied prospectively for the presence or absence of blast cell vacuoles and for any clinical or biological relevance this feature might have. Adequate slides were available from 733 patients (88% of the trial entrants) after five with B ALL were excluded. Vacuolated blast cells (greater than 10%) were present in 204 (28%). The presence of vacuoles was associated with PAS positivity (chi 2 = 27.8; P less than 0.0001), a diagnostic white cell count (WBC) less than 50 x 10(9)/l (chi 2 = 13.1; P less than 0.0001), and the immunophenotype of 'common' ALL (CD10 positive) (chi 2 = 9.1; P less than 0.01). There was no clear association with French-American-British (FAB) type L1 or L2. The 204 patients with vacuoles had a significantly superior disease free survival compared to the remainder (2P = 0.01), a difference which remained significant when the analysis was stratified by FAB type (2P = 0.01), age (2P = 0.02) or sex (2P = 0.02), but which was lost when stratified by WBC (2P = 0.06). These findings provide further evidence that, outside the context of B-ALL, vacuoles are indicative of a relatively benign disease which responds well to therapy. The French-American-British (FAB) classification should be modified to take this into account.